Communication from the governor of Virginia relative to appropriation for Virginia soldiers in the Confederate Army : January 12, 1863 (Document (Virginia. General Assembly. Senate) ;, 1863)
January 12, 1863 Communication from Governor Letcher to the General Assembly regarding providing an appropriation for supplies for wounded Virginia soldiers.